Targeted NMR signal enhancement of RNA by site-directed bis-nitroxide labeling - Rubin Dasgupta; Christian Steinmetzger; Ancy T. Wilson; Satyaki Chatterjee; Gunnar W. Reginsson; Snorri Th. Sigurdsson; Katja Petzold (Proceedings of the National Academy of Sciences, 2026)
MicroRNAs regulate gene expression through sequence-specific interactions with target messenger RNAs (mRNAs), and their misregulation is a hallmark of cancer. MicroRNA-34a (miR-34a), a key modulator of the tumor suppressor p53, binds the mRNA encoding sirtuin 1 (mSirt1) and adopts multiple conformational states that influence repression efficiency. While such dynamics have been characterized in vitro, extending these studies to cellular environments is hampered by weak signals and substantial background inherent to nucleic acid NMR. To overcome this limitation, we developed a site-directed spin labeling strategy for RNA that enables targeted dynamic nuclear polarization (DNP) signal enhancement. Using the bisnitroxide polarizing agent AsymPol-NCS-SDSL, we conjugated spin labels to specific positions of mSirt1 RNA and annealed them to 13 C, 15 N-cytidine-labeled miR-34a. At 9.4 T, we observed up to 27-fold signal enhancements. The selectivity of polarization transfer within the RNA duplex relative to the surrounding environment could be tuned by matrix deuteration, while doping with paramagnetic metal ions accelerated polarization build-up times, with Cu II proving more efficient than Gd III . This work establishes bisnitroxide-based SDSL as a powerful approach for targeted DNP of nucleic acids, enabling high-sensitivity studies of nucleic acids at concentrations ≤40 µ m and paves the way for structural investigations of microRNA–mRNA interactions in cells.